An Investigation of Google Searches for Knee Osteoarthritis and Stem Cell Therapy: What are Patients Searching Online?. Issue 4 (November 2022) - Sullivan, Breanna; Platt, Brooks; Joiner, Josh; Jacobs, Cale; Conley, Caitlin; Landy, David C.; Stone, Austin V.
Background: Stem cell therapies have emerged as a potential treatment for osteoarthritis (OA), but their role remains controversial. Their growing popularity may lead patients to search for information online, but search queries and sources are unknown. Purpose: We sought to (1) identify the most frequently asked questions on Google related to knee OA and stem cell therapy, (2) assess the types of websites accessed through these searches, and (3) evaluate the transparency of these websites. Methods: The search terms "knee, " "osteoarthritis, " and "stem cell" were entered into Google. Frequently asked questions suggested by Google, and their corresponding websites were extracted. Questions and websites were classified by type. Journal of the American Medical Association ( JAMA ) benchmark criteria were used as a measure of website transparency (range: 0–4). Analysis of variance tests were performed to compare JAMA benchmark criteria between website types. Results: Of the 145 questions and website extracted, the most common question subtype pertained to non-stem cell treatments (41.4%) for knee OA; the most common website types were medical publishers (24.8%) and nonacademic medical practices (22.8%). JAMA scores were highest for medical publishers (mean: 3.81) and lowest for nonacademic medical practices (mean: 1.55). Nonacademic medical practices had significantly worse JAMA scores compared with commercial, academic, and medical publishers. Conclusion: The most frequent questions pertained to non-stem cell treatments, although questions related to stem cell efficacy were most common among the 10 most frequent questions. Google searches on knee OA and stem cell therapies often directed the user to websites lacking transparency and verifiable information. Further research is warranted.